2002
DOI: 10.1093/toxsci/66.1.34
|View full text |Cite
|
Sign up to set email alerts
|

A Physiologically Based Pharmacokinetic and Pharmacodynamic (PBPK/PD) Model for the Organophosphate Insecticide Chlorpyrifos in Rats and Humans

Abstract: A PBPK/PD model was developed for the organophosphate insecticide chlorpyrifos (CPF) (O,O-diethyl-O-[3,5,6-trichloro-2-pyridyl]-phosphorothioate), and the major metabolites CPF-oxon and 3,5,6-trichloro-2-pyridinol (TCP) in rats and humans. This model integrates target tissue dosimetry and dynamic response (i.e., esterase inhibition) describing uptake, metabolism, and disposition of CPF, CPF-oxon, and TCP and the associated cholinesterase (ChE) inhibition kinetics in blood and tissues following acute and chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
277
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(301 citation statements)
references
References 61 publications
19
277
2
Order By: Relevance
“…This time period reflects the recognition that TCP is eliminated in urine with a half time of approximately 27 h, so that measurement of urinary TCP on any given day reflects exposures occurring within the previous 3-5 days (Nolan et al, 1984). Similarly, plasma BuChE activity recovers from inhibition with a half time for recovery of approximately 8-9 days, with relatively complete recovery from acute inhibition expected within approximately a month (Nolan et al, 1984;Timchalk et al, 2002b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This time period reflects the recognition that TCP is eliminated in urine with a half time of approximately 27 h, so that measurement of urinary TCP on any given day reflects exposures occurring within the previous 3-5 days (Nolan et al, 1984). Similarly, plasma BuChE activity recovers from inhibition with a half time for recovery of approximately 8-9 days, with relatively complete recovery from acute inhibition expected within approximately a month (Nolan et al, 1984;Timchalk et al, 2002b).…”
Section: Discussionmentioning
confidence: 99%
“…Predicted dose-response relationships for the inhibition of plasma BuChE, RBC AChE and brain AChE as a function of urinary TCPy excretion under conditions of steady-state exposure were generated using the previously developed PBPK/PD model for CPF from Timchalk et al (2002b). The model was run to steady state at a range of absorbed doses from 0.03 to 3000 mg/kg/day, and the percent inhibition of each ChE as a function of urinary TCPy excretion at each steady-state dose rate was recorded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that by using the exposure estimates from Pang et al (2002) as inputs to the PK model (using both steady-state and time-variant assumptions) the TCPy biomarker levels are significantly under-predicted (Figure 4). This under-prediction is likely to be even more severe when the variability in the CPF absorption, which can be as low as 18% (Timchalk et al, 2002b), is taken into account. This leads to the conclusion that the NHEXAS-MDderived exposure estimates are inadequate for use as "prior" exposure information in this particular case.…”
Section: Analysis Of the Linked Pk/biomarker Approach Using Forward Mmentioning
confidence: 99%
“…By physiologic-based pharmaco-kinetic modeling. One can estimate the equilibrium or ''biological equivalent'' blood serum contaminant concentration (mg/dl), which would result from a constant daily dietary intake at the RfD level (Timchalk et al, 2002;Hays et al, 2007). With a physiologic-based pharmaco-kinetic (PBPK) submodel of renal clearance and an assumption of the daily fluid intake (l/day), estimate the average daily urinary contaminant concentration, mg/l, which would be excreted in equilibrium with the calculated blood serum contaminant concentration.…”
Section: Introductionmentioning
confidence: 99%